A deck of 51: Make the most of your unit's staff. Issue 1 (21st April 2016) - Skipworth, Stan
Abstract : Many years ago, the Statler Brothers recorded the hit song "Flowers on the Wall." In it, the lyric "Playin' solitaire till dawn / with a deck of fifty‐one" illustrated the futility of trying to accomplish something when as little as just one piece is missing. That same metaphor could be interpreted in another way.